Investigation and Implementation of Internet of Things (IoT) for Different Applications in Library Services - Shilpa S. Mahajan; Sanjay D. Mahajan (International Journal of Radio Frequency Innovations, 2024)
The purpose of this study is to explore the uses of the Internet of Things (IoTs) and to identify the obstacles associated with deploying IoTs in libraries. The most of the libraries are using limited IoT-based services. IoTs have enormous promise for libraries, since they may provide various services such as self-checkout and self-return, intelligent querying, smart inventory, and more. In this paper, we have examined the areas where IoT can be implemented in academic libraries also various expected difficulties during implementation of IoT in libraries. Further research is done on the various advantages of IoT for library administrations. This study explains the extent of IoTs applications and the challenges to adopt and implement IoTs in libraries. The research findings would be useful for library and administrators who are interested to implement IoTs applications in their libraries for the satisfaction of all concerned stakeholders.
Keywords: Applications of IoT; Internet of Things; Smart Libraries; library services; return